Synthesis and antileishmanial effect of a few cyclic and non-cyclic n-aryl enamino amide derivatives - Behnam Mohammadi-ghalehbin; Sima Najafi; Nima Razzaghi-Asl (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: The prevalence of leishmaniasis is reported in more than 98 countries and Iran is one of the endemic areas. There is no vaccine for this disease and few effective drugs are available to treat it. Moreover, drug resistance to the disease is increasing. During the past decade, several in vitro and in vivo studies have been performed on dihydropyrimidine derivatives as antileishmanial agents. Experimental approach: In the present project, a few 6-methyl-4-aryl-N-aryl dihydropyrimidinone/thiones (A7-A11) and N-heteroaryl-3-(para-methoxy benzyl) amino but-enamides (A1-A6) were synthesized, structurally characterized, and finally subjected to in vitro anti-leishmanial effect against Leishmania major promastigotes. Findings / Results: Results of the study showed that compound A10, 4-(3-chlorophenyl)-6-methyl-N-phenyl- 2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carboxamide, exhibited superior anti-leishmanial effect with IC50 value of 52.67 μg/mL (more active than standard drug Glucantim® with IC50 71000 ± 390 μg/mL). Conclusion and implications: It was demonstrated that some dihydropyrimidine thiones were able to inhibit Leishmania major promastigotes. Structure-activity relationship evaluations indicated that more electron-poor rings such as isoxazole afforded higher activity within A1-A6 series and in these derivatives, N-benzothiazole rings reinforced anti-leishmanial activity concerning thiazole. It was also observed that higher anti-parasite activities of A10 and A11 concerning A7-A9 might be related to the incorporation of the sulfur atom into C2 position, replacement of N-thiazole carboxamide by N-phenyl carboxamide on C5 position of dihydropyrimidine ring, and also replacement of para with meta-substituted phenyls within C4 of dihydropyrimidine ring. The results may help unveil new 4-aryl-5-carboxamide dihydropyrimidines as potential anti-leishmanial agents and their further structural modification toward more potent derivatives.